Accounting for Moral Hazard In Cost-Effectiveness Analysis - Hans Keiding; Bodil O. Hansen (Copenhagen Business School (CBS), Department of Economics, 2007)
In the paper, we use the theory of mechanism design to exhibit the cost of efficient provision of healthcare, defined as the uniquely defined sum of individual side payments which would eliminate moral hazard. It is argued that this cost may be used to assess the costs arising from use of the treatment in cases where it is not appropriate from a strictly medical point of view. An example is given to indicate how this assessment might enter into practical cost-effectiveness analysis.
hdl:10398/7626
Keywords: 330